The Questionnaire in the Interactive Educational Environment as a Means to Form a New Level of a Person’s Consciousness under the Conditions of Informatization of University Education (Journal of Information Technologies in Education (ITE), 2009)
The article deals with possibilities of a questionnaire in the interactive educational environment of Petro Mohyla Black Sea State University installed on the electronic platform MOODLE with the purpose of determining the people’s attitude to different problematic situations of ethic and ecological character, which takes into account the concept of sustainable development and helps to form a new level of a person’s consciousness.
Keywords: a new level of a person’s consciousness; informatization of education; interactive educational environment